MODEL OF DEVELOPMENT OF PEDAGOGICAL ACTIVITY QUALITIES IN STUDENTS THROUGH INDEPENDENT LEARNING (Multidisciplinary Journal of Science and Technology, 2026)
This article proposes an effective model for developing and enhancing students’ pedagogical qualities through the process of independent learning. The study examined students’ pedagogical competencies, their ability to work independently, and readiness for professional activity. Based on models and methodological approaches, the constituent elements of pedagogical qualities were identified, and strategies for integrating them with independent learning tools were developed. The results of the study demonstrated that organizing students’ independent activities in the educational process facilitates the effective formation of pedagogical skills and competencies.